Validation of a dual role of methotrexate-based chitosan nanoparticles in vivo. Issue 52 (10th June 2015) - Hou, Zhenqing; Lin, Jinyan; Li, Yanxiu; Guo, Fuqiang; Yu, Fei; Wu, Hongjie; Fan, Zhongxiong; Zhi, Lili; Luo, Fanghong
<x xml:space="preserve">Abstract</x> Surface functionalization of a PEGylated chitosan nanoparticle with dual-acting methotrexate drives a tumor-targeting effect and also introduces an anticancer effect.